New approaches to the synthesis of pure conjugated polymers - Svoboda, Jan (Acta chimica slovenica, 2006)
This short-review article is based on the lecture presented at the 13th Conference on Materials and Technology held in Portoroz, October 10-12, 2005 and summarizes our recent results obtained in the investigation and development of polymerization methods aimed at the synthesis of high-purity conjugated polymers, polyacetylenes and polyanilines in particular. Part 1. Introduction provides a survey of main procedures currently used in synthesis of conjugated polymersč Part 2. Catalytic chain polymerizations in two-phase systems contains a brief information on the liquid-liquid systems but mainly it deals with a preparation of mesoporous polymerization catalysts and their use and effectivness in the synthesis of high-purity polyacetylenes. The catalyst systems obtained by anchoring of soluble, catalytically active transition-metal complexes on mesoporous supports such as polybenzimidazole beads, all-siliceous molecular sieves MCM 41, MCM 48, and SBA 15, and the sieves with inner pores modified by linkers with -NH2, -PPh2 and -N(PPh2)2 endgroups are discussed as to their activity, stereoselectivity, re-use and transport limitations for guest macromolecules. Part 3. Transformation of stoichiometric polymerizations to catalytic processes mainly deals with the polymerization of aniline and its derivatives with the catalytic system Fe3+žH2O2. Quality of polyanilines prepared by catalytic and stoichiometric procedures are compared and new results are presented, according to which bothactive species present in the reaction mixture, Fe3+ ions and HO radicals, participate in the overall mechanism, creating a synergic system. Concluding Part 4. Conclusions, limitations and perspectives provides a summary of results obtained including advances and limitations of these synthesis approaches and perspectives of their use and development.
Keywords: kataliza; organska kemija; poliacetileni; polianilini; polimeri; polimerizacija